Wind characteristics of Oman - Sulaiman, M.Yusof; Akaak, Ahmed Mohammed; Abd Wahab, Mahdi; Zakaria, Azmi (Elsevier Science, 2002)
Wind data from four stations inOman are analyzed. The sites are located at latitudes from 17°N to 23°N and longitudes from 54°E to 59°E with nearly equal elevation (18 m) from sea level. Data are fitted to the Weibull distribution function. Weibull parameters are derived from the empirical cumulative function and used to calculate the mean wind speed and variance of the theoretical distribution. The goodness of representing the observed distribution with the Weibull distribution is determined using the Kolmogorov- Smirnov (K-S) test. At the 1% and 5% levels of confidence the observed data are well represented by the Weibull distribution. The annual mean values of the wind speed of the observed and theoretical distributions are 2.57 m s-1 and 2.53 m s-1 for Seeb, 2.85 m s-1 and 2.68 m s-1 for Salalah, 5.06 m s-1 and 5.03 m s-1 for Masirah and 5.52 m s-1 and 5.40 m s-1 for Sur respectively. In general wind speed is higher during the summer months, notably June, July and August, and is lower during the winter months of October and November. The monthly mean wind power density varies from 9.71 W m-2 for Seeb in the month of November to 520.85 W m-2 for Sur in the month of August. Both Sur and Masirah have good wind energy potential.